Thuiaria distans Fraser 1914 - Calder, Dale R.; Choong, Henry H. C. (Zenodo, 2018)
Thuiaria distans Fraser, 1914a Thuiaria distans Fraser, 1914a: 197, pl. 32, figs. 123Α, B [invalid junior primary homonym of Thuiaria distans Αllman, 1877]. Thuiaria geniculata Fraser, 1918a: 136 [replacement name for Thuiaria distans Fraser, 1914a, not Thuiaria distans Αllman, 1877]. Salacia fraseri Calder, 1991: 102 [replacement name for Thuiaria distans Fraser, 1914a, not Thuiaria distans Αllman, 1877]. Thuiaria fraseri Cairns et al ., 2002: 26. Type. BCPM 976-00708-001: Canada, British Columbia, Fairway Channel, N of Gabriola Island, 46–55 m, 13 May 1912, one colony, 2.3 cm high, in fair condition, without gonophores. Lectotype, by present designation. BCPM 976-00708-001: Canada, British Columbia, Fairway Channel, N of Gabriola Island, 46–55 m, 13 May 1912, one colony, 2.3 cm high, in fair condition, without gonophores; 60% IPA. Type locality. Canada, British Columbia: Fairway Channel, N of Gabriola Island (Fraser 1914a). Current status. Invalid. Remarks. Fraser (1914a) described Thuiaria distans without designating a type. Nevertheless, a hydroid colony from the type locality in the Fraser Hydroid Collection at the RBCM (BCPM 976-00708-001), listed above, is certain to be a type specimen. Given that Fraser was not explicit in stating the number of colonies in hand as the species was being described, however, we avoid assuming that the specimen is the holotype by monotypy and designate it as the lectotype (ICZN Recommendation 73F). The printed catalogue of the Fraser Collection indicates that the specimen was dry at some point but was rehydrated in January 1984. For all that, it is still in fair condition. Other specimens of the species occur in the Fraser Hydroid Collection at the RBCM (BCPM 976-00709-001: Northwest Bay, 19 June 1914; BCPM 976-00709-002 and BCPM 976-00709-003: Northwest Bay; BCPM 976- 00710-001: 14 km S of Marble Island, 26 June 1935, 347 m), but they are not part of the type series. Thuiaria distans Fraser, 1914a is an invalid junior primary homonym of Thuiaria distans Allman, 1877. Fraser ...